2020
DOI: 10.3389/fpls.2020.00831
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Mapping and Comparative Transcriptome Analysis of Firmness in Watermelon (Citrullus lanatus)

Abstract: Watermelon fruit texture and quality are determined by flesh firmness. As a quality trait, flesh firmness is controlled by multigenes. Defining the key regulatory factors of watermelon flesh firmness is of great significance for watermelon genetic breeding. In this study, the hard-flesh egusi seed watermelon PI186490 was used as the male parent, the soft-flesh cultivated watermelon W1-1 was used as the female parent, and 175 F 2 generations were obtained from selfing F 1 . Primary mapping of the major genes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…The opposite trend of water-soluble pectin with flesh firmness during key developmental stages showed that the firmness change of watermelon flesh has a strong correlation with water-soluble pectin content. Many related studies have shown that during the development and storage of fruits, the decrease in the flesh firmness is often accompanied by the presence of water-soluble pectin (Fils-Lycaon and Buret, 1990;Wei et al, 2010;Gwanpua et al, 2014;Sun et al, 2020), our results are in agreement with previous studies. Ionic-bound pectin is another major type of pectin.…”
Section: Effect Of Cell Wall Contents On the Flesh Firmness Of Watermelon At Different Developmental Stagessupporting
confidence: 93%
“…The opposite trend of water-soluble pectin with flesh firmness during key developmental stages showed that the firmness change of watermelon flesh has a strong correlation with water-soluble pectin content. Many related studies have shown that during the development and storage of fruits, the decrease in the flesh firmness is often accompanied by the presence of water-soluble pectin (Fils-Lycaon and Buret, 1990;Wei et al, 2010;Gwanpua et al, 2014;Sun et al, 2020), our results are in agreement with previous studies. Ionic-bound pectin is another major type of pectin.…”
Section: Effect Of Cell Wall Contents On the Flesh Firmness Of Watermelon At Different Developmental Stagessupporting
confidence: 93%
“…Fruit growth and ripening are also controlled by multiple phytohormones. For instance, ABA regulates fruit ripening in the watermelon 97103, W1-1 and Pi186490 cultivar [60,72]. We identified ABA and MeJA-responsive elements in the ClPSY1 promoter of LSW-177, W1-1 and 97103 cultivars, suggesting that multiple factors involved in hormone synthesis and signaling regulate ClPSY1 expression during fruit ripening.…”
Section: Discussionmentioning
confidence: 85%
“…The nucleotide start site of the ClPSY1 gene was determined using transcription start site (TSS) program of the Softberry software and the cis-regulatory elements were predicted with plantCARE [57] and PLACE [58,59]. The RNA-seq data of watermelon at different ripening stages are available in the NCBI SRA database under the numbers SRX2037189 for cultivar LSW-177 [49] and SUB4001164 for cultivar W1-1 [60]. The expression levels of different transcription factors and ClPSY1 were analyzed at the different stages of fruit ripening.…”
Section: In Silico Analysis Of Clpsy1 Promoter Elements and Related Transcription Factors In Watermelonmentioning
confidence: 99%
“…Transcriptome has made progress in studies on watermelon flesh hardness, color, soluble solids, etc. ( Guo et al, 2015 ; Zhu et al, 2017 ; Gao et al, 2018b ; Sun et al, 2020 ). The transcriptional profiling analysis by K-means clustering has been applied to tomato and other crops earlier ( Srivastava et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%